Distribution of CYP2B6 516G/T pharmacogenetically important polymorphism in the Ukrainian population - Olga Filiptsova; Marina Kobets; Julia Kobets; Olga Naboka; Olga Koiro; Alexandr Ochkur; Larisa Galiy (Elsevier, 2018)
The CYP2B6 is one of the members of the cytochrome P450 superfamily. This enzyme metabolizes a number of currently prescribed drugs and different compounds. In light of clinical significance of the CYP2B6∗6 variant of the CYP2B6 gene, the aim of this study was to investigate the distribution of one of the gene polymorphisms, namely, the 516G/T in the Ukrainian population.The study cohort consisted of 102 healthy Ukrainian adults (48 males, 54 females). Genotyping of the CYP2B6 (rs3745274) polymorphism in the study subjects was carried out using a polymerase chain reaction.The following distribution of 516G/T CYP2B6 genotypes in the Ukrainian cohort was identified: GG - in 56%, GT - in 37% and TT - in 7%. The 516G/T allele frequency of the CYP2B6 gene in population was pG = 0.75 and qT = 0.25, respectively. The population-based sequences were analyzed by the Hardy-Weinberg method.The genetic polymorphism revealed in the Ukrainian population suggests the 516G/T polymorphism of the CYP2B6 genetic testing when prescribing the drugs that are substrates of this gene. Keywords: CYP2B6 (516G/T) polymorphism, Ukraine, Population